Thiamine administration and in-hospital mortality in patients with traumatic brain injury: analysis of the MIMIC-IV database - Gao, Shuangqi; Zhu, Zhendan; Zheng, Wenhan (Frontiers in Neurology, 2025)
AimSeveral studies have suggested the favorable impact of thiamine administration on the prognosis of diseases. However, the value of thiamine in patients with traumatic brain injury (TBI) admitted to the intensive care unit (ICU) remains unclear. The aim of this study was to investigate the association between the between thiamine administration and in-hospital mortality in TBI patients.MethodsA cohort of 1,755 individuals diagnosed with TBI from the Medical Information Mart for Intensive Care IV database were included in this retrospective cohort study. Thiamine administration is determined by the patient’s usage during their stay in the ICU. The primary outcome was in-hospital mortality. Univariable and multivariable Cox regression analysis were used to investigate the relationship between thiamine administration and in-hospital mortality of patients with TBI. Subgroup analysis was also performed to determine if this association differed for subgroups classified using different variables including age (<65 years and ≥65 years), gender (male and female), and the severity of TBI (mild, moderate, and severe).ResultsThe median follow-up time was 6.77 (3.98, 12.94) days, and the in-hospital mortality rate for the population was approximately 14.1%. In the univariable Cox regression analysis, thiamine administration was significantly associated with the reduced risk of in-hospital mortality in TBI patients admitted to the ICU. performing the multivariable Cox regression analysis, the observed association of thiamine administration and in-hospital mortality remained significant, with the hazard ratios (HR) of 0.66 [95% confidence interval (CI) = 0.45–0.98]. In the subgroup analysis, the results demonstrated that thiamine administration resulted in a decreased risk of in-hospital mortality among TBI patients who aged 65 years or older (HR = 0.36, 95% CI: 0.19–0.69), as well as male individuals (HR = 0.36, 95% CI: 0.17–0.80) and those with severe TBI (HR = 0.16, 95% CI: 0.04–0.57).ConclusionThiamine administration may reduce in-hospital mortality for patients with TBI admitted to the ICU.